Audit Committee, Company Size, Leverage and Accounting Conservatism on Tax Avoidance - Yola Christin Lubis; Nurul Ummayro; Tetty Tiurma Uli Sipahutar (Budapest International Research and Critics University, 2022)
This research aims to determine the effect of audit committee, firm size, leverage, and accounting conservatism on tax avoidance. This research uses a sample of the mining sector that is included in the 2017-2019 BEI list. This research uses a quantitative method, with a descriptive type of research. And using the data analysis procedure is multiple linear analysis. Company size proxy is measured by calculating the Natural Logarithm of Total Assets, Leverage through Total DER in the company, accounting conservatism with net income plus depreciation, minus operating cash flow, multiplied by 1, divided by total assets. Tax Avoidance as the dependent variable is measured using the effective tax rate (ETR). The research population was 58 companies and purposive sampling method was used in sampling. So the total number of samples is 47 industries. This research shows simultaneously that the audit committee, firm size, leverage, accounting conservatism do not simultaneously affect tax avoidance. Therefore, this study contributes to providing empirical evidence on the factors that influence tax avoidance in the mining sector.